Trends in CV mortality among patients with known mental and behavioral disorders in the US between 1999 and 2020 - Ebert, Tanya; Hamuda, Nashed; City-Elifaz, Efrat; Kobo, Ofer; Roguin, Ariel (Frontiers in Psychiatry, 2023)
Question: To assess current cardiovascular mortality trends of patients with known mental and behavioral disorders.Findings: in this analysis of over 2.5 million cardiovascular deaths, we observed an increased in age adjusted mortality rate in patients with mental and behavioral disorders. Most prominent increase was observed in substance abuse related mortality, male patients and resident of rural areas.Meaning: our finding may indicate worsening inequity in healthcare access. Efforts must be made to ensure proper healthcare access and risk factor management of this deprived population and improve its cardiovascular health.